Radiation oncology study guide - Hansen, Eric K.; Thomas, Jr., Charles R.; Ord, Celine Bicquart (Springer New York, 2013)
Radiation Oncology Study Guide is a comprehensive study aid for radiation oncology residents preparing for the American Board of Radiology Radiation Oncology Initial Certification board exam. Presenting the fundamental principles of radiation oncology, the book covers the most salient and commonly tested facts on the exam.  Organized by specific disease sites, each chapter presents a series of questions and answers that present clinical features, staging, principles of treatment, and evidence-based studies that guide treatment recommendations, with an emphasis on radiotherapy studies.  The book offers over 1,000 multiple-choice questions with detailed answers and rationales.